1999
DOI: 10.1074/jbc.274.46.33011
|View full text |Cite
|
Sign up to set email alerts
|

Recombinant Human DNA (Cytosine-5) Methyltransferase

Abstract: Initial velocity determinations were conducted with human DNA (cytosine-5) methyltransferase (DNMT1) on unmethylated and hemimethylated DNA templates in order to assess the mechanism of the reaction. Initial velocity data with DNA and S-adenosylmethionine (AdoMet) as variable substrates and product inhibition studies with methylated DNA and S-adenosylhomocysteine (AdoHcy) were obtained and evaluated as double-reciprocal plots. These relationships were linear for plasmid DNA, exon-1 from the imprinted small nuc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
57
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 115 publications
(65 citation statements)
references
References 65 publications
8
57
0
Order By: Relevance
“…Similarly, the stimulatory effect of DNA binding affinity under high concentration of the substrate (40) may account for the slight discrepancy in the estimated substrate preference of Dnmt3a between the ratio under saturating conditions (3.6-fold) and k cat /K m CG under nonsaturating conditions (2.4-fold). Similar to the analyses described in previous reports (14,22,31), secondary plots were generated to analyze the kinetic constants presented in this report. It was confirmed that these values are not significantly different from the results analyzed by the program Sigma Plot/Enzyme Kinetics Module (not shown).…”
Section: Molecular Mechanism Of Dnmt3amentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, the stimulatory effect of DNA binding affinity under high concentration of the substrate (40) may account for the slight discrepancy in the estimated substrate preference of Dnmt3a between the ratio under saturating conditions (3.6-fold) and k cat /K m CG under nonsaturating conditions (2.4-fold). Similar to the analyses described in previous reports (14,22,31), secondary plots were generated to analyze the kinetic constants presented in this report. It was confirmed that these values are not significantly different from the results analyzed by the program Sigma Plot/Enzyme Kinetics Module (not shown).…”
Section: Molecular Mechanism Of Dnmt3amentioning
confidence: 99%
“…Mammalian maintenance DNA methyltransferase DNMT1 has been extensively studied biochemically and enzymatically (14,(27)(28)(29)(30)(31). DNMT1 prefers hemimethylated dsDNA and its kinetic constants have been reported (14,28,29).…”
Section: Construction Expression and Purification Of Mammalianmentioning
confidence: 99%
“…⌬501 and DNMT1 with all of the DNA substrates used and the calculation of the steady-state kinetic constants were as described (29). The concentrations of the reactants and those of the products analyzed were always converted to nanomoles or micromoles per liter and therefore are expressed in nM or M, respectively.…”
mentioning
confidence: 99%
“…Enzyme preparations were Ͼ95% pure (19). Determination of the Kinetic Constants-We previously developed a velocity equation for DNMT1 (29), based on the King-Altman and Cleland methods (30), that considered the enzyme species bound to the AdoMet and unmethylated DNA substrates but not to the AdoHcy and methylated DNA products (initial forward velocity equation). These conditions are met experimentally when the amount of substrate utilized is negligible compared with its total concentration.…”
mentioning
confidence: 99%
See 1 more Smart Citation